Adaptation of Work-Life Balance Strategies in Remote Tourism Destinations: A Case Study of Same Resort Bira Beach - Abdi, Abdi; Rohmah, Irva Yulia; Fajriansyah, Agung (SIGn Journal of Social Science, 2025)
The post-pandemic global tourism industry faces intensive recovery pressures. Work-life imbalance frequently triggers human resource retention crises, particularly in the hospitality sector, which demands 24-hour service excellence. These challenges are increasingly complex for resort hotels in remote tourism destinations that must operate with limited access to professional labor and extreme fluctuations in tourist visitation. This study aims to analyze the adaptation mechanisms of five Work-Life Balance (WLB) strategies—Alternating, Outsourcing, Bundling, Techflexing, and Simplifying—to overcome operational barriers and enhance employee productivity at Same Resort Bira Beach, South Sulawesi. Using a qualitative single-case study design, data were collected through in-depth interviews with management and operational staff. The results reveal significant anomalous findings. First, the use of communication technology (Techflexing) in an isolated environment does not trigger technostress but rather serves as a vital connectivity bridge providing spatial autonomy for employees. Second, integrating resort facilities into the incentive system (Bundling) successfully creates psychological harmonization between work and personal life (Resort-Life Integration). Third, Alternating and Outsourcing strategies are applied tactically as workload safety valves during peak seasons. Overall, this study concludes that in remote destinations, WLB transforms from a mere welfare policy into an effective business survival strategy for maintaining productivity, despite structural challenges posed by short-term target pressures. The study’s implications suggest an adaptive HR management model that leverages locational assets as key retention factors.